Photoresponsive Type III Porous Liquids. Issue 4 (1st December 2022) - Brand, Michael C.; Rankin, Nicola; Cooper, Andrew I.; Greenaway, Rebecca L.
Abstract: Porous materials are the subject of extensive research because of potential applications in areas such as gas adsorption and molecular separations. Until recently, most porous materials were solids, but there is now an emerging class of materials known as porous liquids. The incorporation of intrinsic porosity or cavities in a liquid can result in free‐flowing materials that are capable of gas uptakes that are significantly higher than conventional non‐porous liquids. A handful of porous liquids have also been investigated for gas separations. Until now, the release of gas from porous liquids has relied on molecular displacement (e.g., by adding small solvent molecules), pressure or temperature swings, or sonication. Here, we explore a new method of gas release which involves photoisomerisable porous liquids comprising a photoresponsive MOF dispersed in an ionic liquid. This results in the selective uptake of CO2 over CH4 and allows gas release to be controlled by using UV light. Abstract : Porous liquids have typically focused on static components which require temperature and pressure swings, or sonication, to release gas from the system. Here, a new photoresponsive type III porous liquid is reported, formed by dispersing a known photoresponsive metal–organic framework in an ionic liquid, creating a porous liquid capable of releasing gas upon irradiation with UV light.